Pengembangan Media Flat Math Bebasis Etnomatematika pada Materi Bangun Datar di Sekolah Dasar - Imroatum Mardhiyyah; Via Yustitia; Dian Kusmaharti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is based on the development of 21st century learning, where PowerPoint is one of the applications that support learning with attractive designs. This research is a type of R&D development research with the ADDIE model as the development model. The research population was class II students, with a sample of 10 students from SDN Gempolkerep. The data analysis technique used is the Likert Scale. Flat shape material is introduced at the low grade level, and in this product, the material is associated with local culture, especially the culture in Mojokerto, East Java, which is adjacent to this research area. The results showed that the interactive Flat Math media had been tested for its feasibility and declared fit for use. The validation results of media experts get a percentage of 75% which indicates eligibility, while the results of the validation of material experts get a percentage of 86% which indicates very feasible qualifications. Linguist validation also shows decent results with a percentage of 76%. The average questionnaire results from student respondents show a percentage of 80.4% which indicates that this media is very feasible to use. In addition, the teacher's assessment also gave a percentage of 82%. Based on the data analysis, it can be concluded that Flat Math interactive media is appropriate for use in supporting learning in flat shape material.